Consumer Perceptions of Influencer Authenticity: A Sharia Economic Law Perspective on Generation Z - Nurhilalia Nurhilalia; Muhammad Yusuf; Firman Menne; Yulia Yunita Yusuf (Universitas Muhammadiyah Bandung, 2025)
This study examines how Generation Z consumers in urban Indonesia (West Java) perceive influencer authenticity in online fashion marketing through the lens of Sharia Economic Law. While prior studies have extensively explored influencer authenticity, limited attention has been given to its integration with Islamic legal-ethical principles, particularly within a normative-empirical framework. Moreover, existing research tends to overlook how authenticity is operationalized within Sharia-based ethical boundaries in digital marketing contexts. Addressing this gap, the study draws on fiqh al-muʿāmalāt concepts, including transparency (bayān), honesty (ṣidq), and the prohibition of deception (tadlīs). A qualitative case study approach was employed, involving semi-structured interviews with 20 social media users aged 18–25. Data were analyzed thematically using Braun and Clarke’s (2006) framework with NVivo support. The findings identify five key dimensions of perceived authenticity: transparency and consistency, trustworthiness, relatability (homophily), parasocial interaction, and alignment with Sharia-compliant values. Authenticity functions as a mediating construct linking influencer attributes to consumer trust and ethical judgment. The results further indicate that micro influencers are perceived as more authentic and ethically aligned than celebrity endorsers, while inadequate sponsorship disclosure raises concerns related to gharar and tadlīs. This study contributes theoretically by proposing an integrated authenticity framework grounded in Sharia Economic Law, extending existing influencer marketing literature beyond secular perspectives. As a research implication, it highlights the need to reconceptualize authenticity as a legally and ethically bounded construct in digital marketing contexts. Practically, the findings inform the development of transparent and Sharia-compliant marketing strategies in Muslim-majority markets.